Перерозподiл енергії між резервуаром і рідиною з вільною поверхнею при кутових рухах системи - Лимарченко, О.С.; Семенович, К.О. (Нелінійні коливання, 2016)
Рассматривается задача о движении цилиндрического резервуара с жидкостью на маятниковом подвесе. В начальный момент времени резервуар отклонен от положения равновесия на некоторый угол. Исследовано перераспределение кинетической энергии в системе и объяснено угасание поверхностного волнового движения. Полученные результаты качественно совпадают с экспериментальными данными. The dynamics of a cylindrical tank on the pendulum suspension, partially filled with an ideal liquid, is considered. Initially the reservoir is inclined at some angle. The redistribution of kinetic energy in the system was investigated and analyzed component-wise for different modes of motion in the considered system. The attenuation of surface sloshing processes is explained. The obtained results qualitatively coincide with experimental data.